Analysis of Tourist Satisfaction with Halal Tourism Attributes in the Covid-19 Period - Martaleni, Martaleni; Nasir, Jamal Abdul; Khoiriyah, Rizqiyatul; Djawas, Satya Ramadhany (Journal of Indonesian Tourism and Development Studies, 2025)
Globally, halal tourism is viewed as a niche market with new needs and wants. This has motivated researchers to explore its prospects in Muslim-majority areas. Data were collected from 150 Muslim tourists using a judgment sampling approach. Existing scale instruments measured the social environment, facilities, and food as attributes of halal tourism and their effect on tourist satisfaction. Multiple linear regression was used to analyze the relationships between the research variables. The results confirm that the social environment and food have a significant, but partial, effect on tourist satisfaction. Facilities do not have a significant effect on satisfaction. However, all attributes—social environment, facilities, and food—work together to significantly affect tourist satisfaction at tourist attractions in Batu City. The social environment is the dominant factor influencing tourist satisfaction at Batu City tourism sites.